Improving outcomes of short peripheral vascular access in oncology and chemotherapy administration. Issue 2 (March 2017) - Bertoglio, Sergio; van Boxtel, Ton; Goossens, Godelieve A.; Dougherty, Lisa; Furtwangler, Rhoikos; Lennan, Elaine; Pittiruti, Mauro; Sjovall, Katarina; Stas, Marguerite
A short peripheral intravenous catheter or cannula (PIVC) is frequently used to deliver chemotherapy in oncology practice. Although safe and easy to insert, PIVCs do fail, leading to personal discomfort for patients and adding substantially to treatment costs. As the procedure of peripheral catheterization is invasive, there is a need for greater consistency in the choice, insertion and management of short PIVCs, particularly in the oncology setting where there is a growing trend for patients to receive many different courses of IV treatment over a number of years, sometimes with only short remissions. This article reviews best practice with respect to PIVCs in cancer patients and considers the necessity for bundling these actions. Two care bundles, addressing both insertion and ongoing care and maintenance, are proposed. These have the potential to improve outcomes with the use of short PIVCs for vascular access in oncology practice.